2020
DOI: 10.1080/08276331.2020.1831839
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from entrepreneurial failure through vicarious learning

Abstract: Despite its widespread occurrence, the topic of failure is barely addressed in entrepreneurship education. Consequently, students are given an incomplete and unrealistic picture of the complexity of being entrepreneurs. This study explores the pedagogical potential of introducing vicarious learning about failure in educational programs rather than focusing solely on starting, growing and success. Taking a qualitative approach, this study examined students' reflective reports written after an interview with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Bolinger and Brown (2015) argue that the role of EE is to acknowledge both costs and benefits of failure in order for students to acknowledge its complexity. Finally, Alvarado Valenzuela et al. (2020) propose vicarious learning as a safe approach in an educational situation for students to increase their knowledge and positive perception of the role of failure by drawing on someone else's experience.…”
Section: Unpacking the Content Of A Model For The Entrepreneurial Min...mentioning
confidence: 99%
“…Bolinger and Brown (2015) argue that the role of EE is to acknowledge both costs and benefits of failure in order for students to acknowledge its complexity. Finally, Alvarado Valenzuela et al. (2020) propose vicarious learning as a safe approach in an educational situation for students to increase their knowledge and positive perception of the role of failure by drawing on someone else's experience.…”
Section: Unpacking the Content Of A Model For The Entrepreneurial Min...mentioning
confidence: 99%
“…Empathy also is crucial to educators, who must attend to the perspectives of students, and researchers, who must understand the perspectives of both research subjects and readers of academic articles. The consumption of fiction can offer learners a vicarious experience of entrepreneurial work (Dust, 1981; Alvarado Valenzuela et al, 2020).…”
Section: Embracing Fiction As a Resource For Founders And Teachersmentioning
confidence: 99%
“…In fact, a previous study called attention to the positive effects of vicarious failures. For example, in a related study in the entrepreneurial pedagogy literature, Alvarado Valenzuela et al (2020) showed the positive effects of vicarious business failures from entrepreneurship training perspectives. This study reported that students who interviewed entrepreneurs about their previous failures developed a sense of realism about running their business ventures.…”
Section: Vicarious Efs and Entrepreneurial Identity Aspirationmentioning
confidence: 99%
“…In fact, research suggests that EFs could help entrepreneurs learn from failures through a long-term process (Klimas et al, 2021). Those entrepreneurs who successfully managed their failures and initiated subsequent entrepreneurial activities can exert a positive effect on others in the community by transferring their learned lessons, as suggested by Alvarado Valenzuela et al (2020).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation